The Sac1 lipid phosphatase regulates cell shape change and the JNK cascade during dorsal closure in Drosophila. - Wei, H.C.; Sanny, J.; Shu, H.; Baillie, D.L.; Brill, J.A.; Price, J.V.; Harden, N. (Current Biology, 2003)
The Sac1 lipid phosphatase dephosphorylates several phosphatidylinositol (PtdIns) phosphates and, in yeast, regulates a diverse range of cellular processes including organization of the actin cytoskeleton and secretion. We have identified mutations in the gene encoding Drosophila Sac1. sac1 mutants die as embryos with defects in dorsal closure (DC). DC involves the migration of the epidermis to close a hole in the dorsal surface of the embryo occupied by the amnioserosa. It requires cell shape change in both the epidermis and amnioserosa and activation of a Jun N-terminal kinase (JNK) MAPK cascade in the leading edge cells of the epidermis [2]. Loss of Sac1 leads to the improper activation of two key events in DC: cell shape change in the amnioserosa and JNK signaling. sac1 interacts genetically with other participants in these two events, and our data suggest that loss of Sac1 leads to upregulation of one or more signals controlling DC. This study is the first report of a role for Sac1 in the development of a multicellular organism.